Assessing socially acceptable locations for onshore wind energy using a GIS-MCDA approach. (6th March 2019) - Harper, Michael; Anderson, Ben; James, Patrick; Bahaj, AbuBakr
Abstract: In the context of Great Britain, onshore wind provides the most cost-effective method of renewable electricity generation. However, projects often face opposition to development based on social issues, and there are concerns that existing geospatial modelling approaches fail to fully integrate these effects into their assessment. Building upon previous statistical analysis, this paper presents a geospatial multi-criteria decision analysis that integrates the technological, legislative and social constraints to determine suitable sites for onshore wind turbine development in Great Britain. The findings suggest that the capacity estimates for wind are less than 5% of what was previously estimated, yet opportunities remain for further exploitation of this resource.